2022
DOI: 10.1101/2022.09.25.22279830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase-Amplitude Coupling in Autism Spectrum Disorder: Results from the Autism Biomarkers Consortium for Clinical Trials

Abstract: Background: Autism spectrum disorder (ASD) is defined behaviorally, but measures that probe underlying neural mechanisms may provide clues to biomarker discovery and brain-based patient stratification with clinical utility. Phase-amplitude coupling (PAC) has been posited as a measure of the balance between top-down and bottom-up processing in cortex, as well as a marker for sensory processing and predictive coding difficulties in ASD. We evaluate differences in PAC metrics of resting-state brain dynamics betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A recent EEG study comparing children with autism and typically developing controls, aged 6-11 years identified a notable increase in alpha-gamma and theta-gamma PAC strength in the autism group. Additionally, the study revealed significant correlations between whole-brain theta-gamma PAC strength with autism severity scores on social communication abilities, IQ and levels of restricted and repetitive behaviors across both cohorts (50). This is consistent with our results from FXS mouse model, where the strength of PAC, measured between the amplitude of the gamma band and the phase of lower frequency oscillations (4–12 Hz), is higher in KO female mouse models compared to WT controls.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A recent EEG study comparing children with autism and typically developing controls, aged 6-11 years identified a notable increase in alpha-gamma and theta-gamma PAC strength in the autism group. Additionally, the study revealed significant correlations between whole-brain theta-gamma PAC strength with autism severity scores on social communication abilities, IQ and levels of restricted and repetitive behaviors across both cohorts (50). This is consistent with our results from FXS mouse model, where the strength of PAC, measured between the amplitude of the gamma band and the phase of lower frequency oscillations (4–12 Hz), is higher in KO female mouse models compared to WT controls.…”
Section: Discussionmentioning
confidence: 93%
“…Cross-frequency coupling has been developed as a method to assess moment-to-moment interaction between oscillations of different frequencies within EEG signals (50). PAC assesses how the amplitude of high-frequency activity is modulated by the phase of low-frequency oscillations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For MSE, scale was divided into four ranges: all (1-20), ne (1-7), medium (8-13), coarse (14)(15)(16)(17)(18)(19)(20). MSE within each channel was averaged across these scale ranges.…”
Section: Channel Groupings For Comparisonsmentioning
confidence: 99%
“…12 Peak alpha frequency has been reported to be higher in children with autism than in neurotypical children, 13 but also lower in autistic children than in neurotypical children. 14 Similarly, some autistic participants have exhibited greater PAC between theta phase and gamma power than neurotypical individuals, 15 other autistic participants have exhibited increased PAC between alpha and gamma oscillations, 13 but yet other autistic participants have exhibited speci c regional decreases as well as increases in PAC between alpha and gamma oscillations. 16 Autistic individuals generally exhibit decreases in low frequency connectivity, 17 but some studies have reported increases, 18 and complex patterns of changes in network connectivity topology have also been reported.…”
Section: Introductionmentioning
confidence: 99%